INTEGRATION OF ISLAM AND LOCAL CULTURE: Tandhe’ in Madura - Mohammad Hidayaturrahman (State Islamic University North Sumatra, 2018)
Abstract: Religion with culture often has a collision. But in Madura, between religion and culture can walk together. This research analyzes how the integration between local culture in Madura especially tandhe’ culture with Islam, as well as what role local actors in realizing a harmonious life. The theory used in this research is the theory of cultural integration of Emile Durkheim. This research method using phenomenology, with descriptive qualitative approach. This research was conducted by observation and interview. There is an integration between Muslims and the local culture of tandhe’, in the form of presenting a culture of tandhe’ in marriage activities conducted in an Islamic way. There is the role of actors in creating a harmonious life between Muslims and the culture of tandhe’, ranging from religious leaders, and people involved in tandhe’.Abstrak: Integrasi Islam dengan Budaya Lokal: Tandhe’ in Madura. Agama dengan budaya seringkali mengalami benturan. Tetapi di Madura, antara agama dengan budaya bisa berjalan bersama. Penelitian ini menganalisis bagaimana integrasi antara budaya lokal di Madura khususnya budaya tandhe’ dengan Islam, serta seperti apa peran aktor lokal dalam mewujudkan kehidupan yang harmonis. Teori yang digunakan dalam penelitian ini adalah teori integrasi budaya Emile Durkheim. Metode penelitian ini menggunakan fenomenologi (phenomenology), dengan pendekatan kualitatif deskriptif. Penelitian ini dilakukan dengan melakukan pengamatan/observasi dan wawancara. Ditemukan adanya integrasi antara kaum Muslim dengan budaya lokal tandhe’, dalam bentuk menghadirkan budaya tandhe’ dalam kegiatan pernikahan yang dilakukan secara islami. Ada peran para aktor dalam menciptakan kehidupan harmonis antara kaum Muslim dengan budaya tandhe’, mulai dari tokoh agama dan orang-orang yang terlibat di dalam tandhe’.Keywords: local culture, integration, harmonious, Madura, tandhe’